Peningkatan Peran Strategis Litbang dalam Pemantapan Otonomi Daerah di Propinsi Papua - Hartopo, Agus (Jurnal Bina Praja, 2009)
With the regional autonomy policy as mandated by Law No. 32 of 2004 concerning Regional Government, that regions are given broad authority to manage and regulate all government affairs, where regions have the authority to make regional policies in accordance with the objectives of regional autonomy to accelerate the realization of community welfare through improving services, community empowerment and community participation, in accordance with the potential characteristics of the region. For this reason, research and development are needed to solve the problems faced so that regional autonomy can succeed steadily, effectively and efficiently, especially in Papua Province. This writing is based on observations and observations as well as experience, which are intended for the need to increase the strategic role of research and development in strengthening autonomy in Papua Province. So that the potential and characteristics of Papua Province can be utilized to truly accelerate community welfare.